2019 IEEE 62nd International Midwest Symposium on Circuits and Systems (MWSCAS) 2019
DOI: 10.1109/mwscas.2019.8884910
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating Deterministic and Stochastic Binarized Neural Networks on FPGAs Using OpenCL

Abstract: Recent technological advances have proliferated the available computing power, memory, and speed of modern Central Processing Units (CPUs), Graphics Processing Units (GPUs), and Field Programmable Gate Arrays (FPGAs). Consequently, the performance and complexity of Artificial Neural Networks (ANNs) is burgeoning. While GPU-accelerated Deep Neural Networks (DNNs) currently offer state-of-the-art performance, they consume large amounts of power. Training such networks on CPUs is inefficient, as data throughput a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…These tools allow engineers to describe their targeted hardware in high-level programming languages such as C to synthesize them to Register Transfer Level (RTL). The tools then offload the computationalcritical RTL to run as kernels on parallel processing platforms such as FPGAs [91].…”
Section: B Fpga Dnnsmentioning
confidence: 99%
“…These tools allow engineers to describe their targeted hardware in high-level programming languages such as C to synthesize them to Register Transfer Level (RTL). The tools then offload the computationalcritical RTL to run as kernels on parallel processing platforms such as FPGAs [91].…”
Section: B Fpga Dnnsmentioning
confidence: 99%
“…B INARIZATION has been used to augment the performance of Deep Neural Networks (DNNs), by quantizing network parameters to binary states, replacing many resourcehungry multiply-accumulate operations with simple accumulations [1]. It has been demonstrated that Binarized Neural Networks (BNNs) implemented on customized hardware can perform inference faster than conventional DNNs on stateof-the-art Graphics Processing Units (GPUs) [2], [3], while offering notable improvements in power consumption and resource utilizations [4]- [6]. However, there is still a performance gap between DNNs and conventional BNNs [7], which binarize parameters deterministically or stochastically.…”
Section: Introductionmentioning
confidence: 99%
“…Binarized Neural Networks (BNNs) [2], which perform binary MAC computations during forward and backward propagations, have demonstrated comparable performance to conventional DNNs, while significantly reducing resource and power utilizations [3]. On account of endurance concerns, ReRAM devices are ill-suited for implementing backward propagations, required during the training routine of BNNs where a large number of programming cycles are required.…”
Section: Introductionmentioning
confidence: 99%